2009
DOI: 10.1007/s00405-009-1157-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of velopharyngeal insufficiency by autologous fat injection

Abstract: Velopharyngeal insufficiency (VPI) is a structural or functional trouble, which causes hypernasal speech. Velopharyngeal flaps, speech therapy and augmentation pharyngoplasty, using different implants, have all been used to address this trouble. We hereby present our results following rhinopharyngeal autologous fat injection in 18 patients with mild velopharyngeal insufficiency (12 soft palate clefts, 4 functional VPI, 2 myopathy). 28 injections were carried out between 2004 and 2007. The degree of hypernasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…Autologous free fat grafting is a widely accepted technique used for the correction of various soft-tissue defects because it is biocompatible, versatile, natural-looking, non-immunogenic, inexpensive, and readily obtainable with low donor site morbidity [1,2]. Although free fat grafting is used as a method for soft tissue reconstruction, absorption of the fat after grafting is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous free fat grafting is a widely accepted technique used for the correction of various soft-tissue defects because it is biocompatible, versatile, natural-looking, non-immunogenic, inexpensive, and readily obtainable with low donor site morbidity [1,2]. Although free fat grafting is used as a method for soft tissue reconstruction, absorption of the fat after grafting is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Dejonckere [3,12,22]. All studies reported good results, but only Leuchter's used Borel-Maisonny scale as clinical criteria, making a comparison possible.…”
Section: Discussionmentioning
confidence: 90%
“…AFT has been proposed for treatment of VPI since the beginning of the 20th century [3], but there is sparse evidence in the literature Objective: To assess the efficiency of autologous fat transfer (AFT/Coleman procedure) in the management of velopharyngeal insufficiency (VPI). Settings: Tertiary academic center, retrospective case series over a 4 year period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The results of velopharyngoplasties are excellent in reducing hypernasality and improving voice resonance and speech articulation; however, they may cause considerable postoperative morbidity in terms of pain and bleeding. 9 Fat grafting in the posterior pharyngeal wall using an external approach was originally described by Gaza 10 in 1926. 3,4 Augmenting the posterior pharyngeal wall by means of implants or reabsorbable materials has been proposed as an alternative to major surgical procedures over the years, 5,6 but the main limitations of implants are related to their migration and extrusion and foreign body reaction, 7 and reabsorbable materials only lead to temporary improvement.…”
mentioning
confidence: 99%